2015 ACC/AHA/SCAI Focused Update on Primary Percutaneous Coronary Intervention for Patients With ST-Elevation Myocardial Infarction: An Update of the 2011 ACCF/AHA/SCAI Guideline for Percutaneous Coronary Intervention and the 2013 ACCF/AHA Guideline for the Management of ST-Elevation Myocardial Infarction. Issue 11 (15th March 2016) - Levine, Glenn N.; Bates, Eric R.; Blankenship, James C.; Bailey, Steven R.; Bittl, John A.; Cercek, Bojan; Chambers, Charles E.; Ellis, Stephen G.; Guyton, Robert A.; Hollenberg, Steven M.; Khot, Umesh N.; Lange, Richard A.; et al.
Abstract : Supplemental Digital Content is available in the text.